2013
DOI: 10.3892/etm.2013.1461
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the efficacies of curcumin and puerarin in C57BL/6 mice with steatohepatitis induced by a methionine- and choline-deficient diet

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a prevalent disease, which features an abnormal accumulation of lipids inside hepatocytes. Steatohepatitis plays a critical role in the process resulting in liver fibrosis and cirrhosis. Curcumin and puerarin are herbal products widely used in Asia, which are believed to have therapeutic benefits for alleviating the symptoms of steatohepatitis. In this study, mice models of steatohepatitis induced by a methionine- and choline-deficient diet (MCD) were established to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
(41 reference statements)
3
25
0
Order By: Relevance
“…[25][26][27][28] Furthermore, it has been shown to have clinical applications in the treatment of coronary heart disease and diabetic nephropathy. [29][30][31] The previous study found that Puerarin may induce therapeutic angiogenesis in myocardium by inducing VEGF and eNOS expression in myocardium of rat with myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] Furthermore, it has been shown to have clinical applications in the treatment of coronary heart disease and diabetic nephropathy. [29][30][31] The previous study found that Puerarin may induce therapeutic angiogenesis in myocardium by inducing VEGF and eNOS expression in myocardium of rat with myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese herbs have been traditionally used for treating liver disease worldwide (37), and there are numerous herbal products that are believed to benefit patients with NAFLD, with acceptable levels of safety. For example, previous studies have demonstrated that puerarin, baicalin and berberine, which are three major constituents of the Chinese herbs: Puerariae Radix, Scutellariae Radix and Coptidis Rhizoma, exhibit therapeutic effects on rats with NAFLD (20)(21)(22). However, there have been few reports regarding the compatibility of these constituents.…”
mentioning
confidence: 98%
“…1A-C), are three major constituents of the Chinese herbs: Puerariae Radix [roots of Pueraria lobata (Willd.) Ohwi, PR], Scutellariae Radix (roots of Scutellaria baicalensis Georgi SR) and Coptidis Rhizoma (rhizomes of Coptis chinensis Franch, CR), which have demonstrated therapeutic effects on rats models of NAFLD (20)(21)(22). It is believed that a combination of agents may effectively reduce side effects and improve adaptive resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Its use in in vivo models of NASH reveals an improvement of steatosis, inflammation, ballooning and fibrosis, and a reduction of blood serum monocyte chemoattractant protein (MCP)-1, TNFα and IL-6 levels. Lipoperoxidation is attenuated, the antioxidant status is enhanced, and the expressions of NF-κB, suppressor of cytokine signaling 3 (SOCS3), SREBP-1c, FAS, ACC and 3-hydroxy-3-methylglutaryl (HMG)-CoA reductase are decreased in the liver after curcumin treatment [80,106,107]. The beneficial effects of curcumin on steatosis and inflammation could be mediated by the STAT3 signaling activation and the improvement of mitochondrial function [107].…”
Section: Fig (2)mentioning
confidence: 99%
“…This isoflavone is able to diminish steatosis, inflammation and ballooning by reducing triglyceride and cholesterol levels and TNFα expression in the liver, and improving leptin signal transduction through janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) pathways [78][79][80].…”
Section: Isoflavonesmentioning
confidence: 99%